2012
DOI: 10.14429/dsj.62.2395
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Carbon-Carbon Threaded Fasteners for High Temperature Applications

Abstract: Carbon-Carbon (C-C) threaded fasteners have been developed for joining C-C composites experiencing temperature above 1500 °C. The fasteners were fabricated from spun yarn graphitized carbon fabric through resin route and from needle punched carbon felt through pitch route techniques. The preforms were processed with multiple cycles of impregnation, carbonisation, and graphitisation up to densities of 1.78 gcm -3 and 1.90 gcm -3. Densification process cycles were repeated to obtain composites with reduced poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Mei et al (2010) reported carbon fiber cloth reinforced 2D C/SiC bolts with the tensile strength of 210-230 MPa by CVI process. Kushwaha et al (2012) fabricated carbon-carbon (C/C) threaded fasteners from spun yarn graphitized (SYG) carbon fabric through resin route and from needle-punched (NP) carbon felt through pitch route techniques with tensile strengths of 102 MPa and 103 MPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei et al (2010) reported carbon fiber cloth reinforced 2D C/SiC bolts with the tensile strength of 210-230 MPa by CVI process. Kushwaha et al (2012) fabricated carbon-carbon (C/C) threaded fasteners from spun yarn graphitized (SYG) carbon fabric through resin route and from needle-punched (NP) carbon felt through pitch route techniques with tensile strengths of 102 MPa and 103 MPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers worldwide have studied one or the other preforms mostly using PIP, LSI and CVI + PIP process for making composite fasteners (Verrilli et al 2002;Böhrk et al 2010;Wan 2005;Zhang et al 2011;Mei et al 2010;Kushwaha et al 2012), but to the best of our knowledge, a comparison amongst different possible orientations of continuous fibre preform architectures for realizing nearnet-shaped composite fasteners using CVI process is not reported. There are different methodologies available for fabrication of continuous fibre preforms such as alternate stacking of carbon fabric plies in the order of 0°/90°/ ± 45° followed by stitching (termed as 2D stitched preform), weaving of carbon fibres along mutually orthogonal directions (3D woven preform) and NOOBing (Non-interlacing, Orienting Orthogonally and Binding) technique described by Khokar (2002) as a non-woven three-dimensional fabric-forming process which could be utilized for fabrication of near-net-shaped composite fasteners (4D/5D NOO-BED preform).…”
Section: Introductionmentioning
confidence: 99%